Working models of human perception - Elsendoorn, Ben A. G.; Bouma, Herman (Academic Press, 1989)
This book devotes attention to both theoretical and applied problems simultaneously. Many applied problems turn out to be very difficult and they often need deep theoretical insight in order to get solved. In fact, applied problems often serve as a source of inspiration for theoretical work, since they usually are beyond reach of present theories and may show us in what direction theories need to be developed. The layout of the book is a reflection of the three main areas of research at the Institute for Perception Research: Hearing and Speech, Vision and Reading, Cognition and Communication. Following the set-up of the workshop, the organization of the papers is in pairs, such that the odd-numbered chapters are generally reactions to the even-numbered chapters.